2022
DOI: 10.1126/sciadv.abj8618
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the biogenesis of forward programmed megakaryocytes from induced pluripotent stem cells

Abstract: Platelet deficiency, known as thrombocytopenia, can cause hemorrhage and is treated with platelet transfusions. We developed a system for the production of platelet precursor cells, megakaryocytes, from pluripotent stem cells. These cultures can be maintained for >100 days, implying culture renewal by megakaryocyte progenitors (MKPs). However, it is unclear whether the MKP state in vitro mirrors the state in vivo, and MKPs cannot be purified using conventional surface markers. We performed single-cell RNA s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…In this case, plate-based or combinatorial indexing methods form a good alternative. Other studies [ 92 , 93 , 94 , 95 ] have, however, successfully constructed high-quality MK libraries using 10X Chromium. Table 1 compares the advantages of the two most frequently used scRNA-seq methods, plate-based and droplet-based.…”
Section: Single-cell Transcriptomics Of Healthy Megakaryocytesmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, plate-based or combinatorial indexing methods form a good alternative. Other studies [ 92 , 93 , 94 , 95 ] have, however, successfully constructed high-quality MK libraries using 10X Chromium. Table 1 compares the advantages of the two most frequently used scRNA-seq methods, plate-based and droplet-based.…”
Section: Single-cell Transcriptomics Of Healthy Megakaryocytesmentioning
confidence: 99%
“…In Sun et al [ 91 ], three MK subpopulations were reported with distinct transcriptomes linked to the inflammatory response, HSC niche interactions and platelet generation. scRNA-seq has also driven transcriptomic research into primary MK cells [ 89 , 94 ], for which extensive sample purification is needed, most often through flow cytometry [ 90 , 99 ]. The study of Lu et al [ 90 ] identified key genes involved in MEP fate determination and demonstrated that differential modulation of cell cycle speed dictates MEP differentiation into either erythrocytes or megakaryocytes using scRNA-seq.…”
Section: Single-cell Transcriptomics Of Healthy Megakaryocytesmentioning
confidence: 99%
See 3 more Smart Citations